Differential effects of spatial network structure and scale on population size and genetic diversity of the ninespine stickleback in a remnant wetland system. (29th December 2014) - Ishiyama, Nobuo; Koizumi, Itsuro; Yuta, Teru; Nakamura, Futoshi
Summary The management of population size and genetic diversity in fragmented landscapes is the central issue in conservation biology. Functional connectivity between remnant habitat patches affects these parameters. However, the functional connectivity for genetic diversity would be characterised by a greater spatial scale than population size even within the same habitat network. The reason for this difference is that while dispersal frequency generally decreases with increasing distance, only a few immigrants may effectively contribute to gene flow, whereas a certain number of dispersers may be required to influence population abundance. Here, we investigated the effects of habitat network structures on population abundance and genetic diversity of the ninespine stickleback, Pungitius pungitius, in remnant wetland ponds in northern Japan. We tested (i) whether both population abundance and genetic diversity are positively related not only to habitat size but also to connectivity and (ii) whether the dispersal effect extends to greater spatial scales in genetic diversity than in population size. We employed a graph theoretical index to measure the degree of pond connectivity. This index can evaluate the connectivity threshold distance above which individuals cannot disperse and clarify the difference in the spatial scale of effective dispersal between population abundance and genetic diversity. Pond connectivity significantly affected the spatial variation of both population abundance and genetic diversity. In contrast, pond size was related only to population abundance. As we predicted, the connectivity threshold distance for genetic diversity was more than two times greater than that for population abundance (12.5 km versus 5 km, respectively). Our findings indicate that the landscape managers should consider various spatial scales as a conservation unit for the management of a habitat network in accordance with the conservation targets that they establish. We also found that small artificial agricultural ditches and streams may play important roles in sustaining the population networks of wetland organisms.